The Paradoxical Protective Effect of Liver Steatosis on Severity and Functional Outcome of Ischemic Stroke - Baik, Minyoul; Kim, Seung Up; Nam, Hyo Suk; Heo, Ji Hoe; Kim, Young Dae (Frontiers in Neurology, 2019)
Background: There is very limited information on the relationship between non-alcoholic fatty liver disease (NAFLD) and the severity or functional outcomes of ischemic stroke or transient ischemic stroke (TIA). We investigated the correlation between NAFLD and stroke outcomes. Methods: NAFLD was assessed in 321 patients with first-ever acute ischemic stroke or TIA, who underwent transient elastography from January 2014 to December 2014. The association of liver steatosis with stroke severity, assessed using the National Institute of Health Stroke Scale (NIHSS), was investigated using robust regression analysis. We also compared the functional outcome at 90 days according to the presence or burden of liver steatosis. Results: NAFLD was observed in 206 (64.2%) patients. Patients with NAFLD had less severe stroke (median NIHSS score 2 vs. 3, P = 0.012) and more favorable functional outcome at 90 days (85.3 vs. 70.5, P = 0.004). Patients with NAFLD were likely to have a 23.3% lower (95% confidence interval [CI], -39.2% to -3.2%, P = 0.026) NIHSS score and a 2.5-fold higher (95% CI, 1.08–5.67, P = 0.033) possibility of favorable functional outcome in multivariate analysis. Conclusions: Our study shows that a higher burden of liver steatosis seems to be associated with less severe stroke and better functional outcome after ischemic stroke or TIA.